INFORMATION SUPPORT OF SCIENCE AND EDUCATION: REQUIREMENTS OF TIME (FROM THE EXPERIENCE OF SCIENTIFIC AND TECHNICAL LIBRARY OF IVANO-FRANKIVSK NATIONAL TECHNICAL UNIVERSITY OF OIL AND GAS) - Pylyp, Yaroslava A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This article describes the information support of users of scientific and technical library of Ivano-Frankivsk National Technical University of Oil and Gas, a combination of traditional methods with the latest information technologies, the interaction of the library and information educational environment of the University